Metabolic Syndrome Among Physicians: A Pilot Study from Chattogram, Bangladesh - Awal, Anisul; Ahmed, Farid Uddin (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background : Although the information on Metabolic Syndrome (MetS) in the general population from different parts of Bangladesh is available, the information regarding the same is scarcely available from physicians of Bangladesh. This study was aimed to assess the prevalence of MetS among physicians working at Chattogram Medical College Hospital, Bangladesh. Materials and methods : Data was collected for this cross-sectional study from 255 working physicians of Chittagong Medical College Hospital in 2018. The participants filled a structured questionnaire followed by physical and biochemical measurements including waist circumference, blood pressure, lipid profile, and fasting blood glucose. National Cholesterol Education Program’s Adult Treatment Panel III report (ATP III) defines criteria were used to identify physicians with the MetS. Results : Among 255 participants (males - 192 and females - 63), 100 (39.2%) were with MetS. Prevalence of same was higher in females (41.3%) than males (38.5%). The elderly physicians (>40 years) had a higher prevalence compared to the younger (£40 years) physicians [72 (50.3%) vs. 28 (25.0%)]. In the males, low High-Density Lipoproteins-Cholesterol (HDL-C) was the major contributor to the prevalence of MetS followed by high blood pressure. However, in females, low HDL-C and greater waist circumference contributed the maximum to MetS. Conclusion : This study showed a high prevalence of MetS among physicians of Bangladesh, and thereby warrants the urgent implementation of preventive health care strategies to reduce both morbidity and mortality related to this medical problem. Further studies ought to focus on the working conditions and lifestyles of individuals in these high-risk groups. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 65-68